EFEKTIVITAS BABY MASSAGE TERHADAP STATUS GIZI PADA BAYI DI KLINIK PRATAMA ARRABIH KOTA PEKANBARU - Nur Israyati; Yulrina Ardhiyanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Nutritional status is an indicator in determining a child's health status. A good nutritional status can help the child's growth and development process to reach optimal maturity. The purpose of this study was to determine the effectiveness of baby massage on the nutritional status of infants. After this, it is hoped that it can increase the baby's appetite so that the nutritional status can be overcome with baby massage therapy that can be done by the parents themselves. Handling of malnutrition status can be done by giving the baby a balanced nutritional intake through his mother with exclusive breastfeeding and baby massage. Baby massage therapy provides benefits including, Increases endurance, improves blood circulation and respiration, stimulates digestive and disposal functions, increases weight gain, reduces stress and tension, increases alertness, makes deep sleep, reduces pain, reduces bloating and abdominal pain, Increasing the inner relationship between parents and babies, Increasing the production of breast milk, Helping parents know the language / non-verbal / verbal signs of babies, Creating self-confidence in caring for babies. The research method used in achieving the objectives of this study was an experiment with a Quasi Experiment research type with a Pretest-Post test design, by observing twice, namely before and after treatment. The population in this study were all infants aged 1-12 months as many as 34 infants using accidental sampling. The results showed the effectiveness of baby massage on the nutritional status of infants. The Wilcoxon and Mann-Whitney statistical test shows a significant p value of 0.01 (p